The Effect of Transformational Leadership, Quality of Work-Life on Organizational Citizenship Behavior with Organizational Commitment Mediation - Dachlyani Yustina Dewi; Yudi Nur Supriadi; Acim Heri Iswanto (Journal of Social Science, 2022)
The purpose of this quantitative study was to determine the effect of Transformational Leadership (TL), Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB) with Organizational Commitment (OC) Mediation. ASN Civil servants millennial employees of the Human Resources Development Training and Education Unit of the Ministry of Law and Human Rights are the population in this study.The criteria for respondents using purposive sampling technique. The number of samples used in this study were 100 respondents, using simple random sampling method. Data collection was done by distributing questionnaires. The analysis technique of this research uses Structure Equation Models (SEM) analysis using Partial Least Square (PLS). This study shows that (1) TL has a significant effect on OCB with a path coefficient value of 0.375 with a Tstatistic value of 3.116 > 1.96 (2) QWL has no significant effect on OCB with a path coefficient value of 0.163 with a Tstatistic value of 1.400 < 1.96 (3) TL has an effect significant effect on OC with a path coefficient value of 0.263 with a Tstatistic value of 2.846 > 1.96 (4) QWL has a significant effect on OC with a path coefficient value of 0.462 with a Tstatistic value of 5.506 > 1.96 (5) OC has a significant effect on OCB with a path coefficient value of 0.315 with Tstatistic value 3.765 > 1.96.